INVESTIGATION OF DIFFERENCES IN P53 GENE POLYMORPHISMS BETWEEN SCHIZOPHRENIA AND LUNG CANCER PATIENTS IN THE TURKISH POPULATION - Ozbey, Ulku; Yuce, Huseyin; Namli, Mustafa; Elkiran, Tamer (Wiley-Blackwell, 2009)
[Abstract Not Available]